EXPENDITURE PATTERN AMONG INDONESIAN MANUFACTURING WORKERS: CASE STUDY IN PULAU PINANG - Siti 'Aisyah Baharudin (Universitas Ahmad Dahlan, 2020)
This study is conducted to provide an understanding of the pattern of expenditure among Indonesian female manufacturing worker’s remittances in Malaysia. A total of 100 Indonesian women workers were randomly selected. The location of the study is two manufacturing companies in Penang. Structured interview questions are used to analyze descriptive data. In this study, most of the respondents earn monthly income of RM1000-RM1999 with 44 % and monthly living cost is between RM1-RM499. There are four main variables that determine the respondents' expenditure pattern; remittance, debt, entertainment, and food expenditure. The result found that 84 % of respondents always send money to Indonesia every month. Furthermore, 42 % of respondents have debt. There are 81 % of respondents who always spend their money for entertainment purposes and 53 % of respondents choose to buy a ready food.